2015
DOI: 10.1080/00397911.2015.1096943
|View full text |Cite
|
Sign up to set email alerts
|

Direct Preparation of Amides from Amine Hydrochloride Salts and Orthoesters: A Synthetic and Mechanistic Perspective

Abstract: The conversion of a wide range of primary, secondary aliphatic and a few arylamine hydrochloride salts to their corresponding acetamides with trimethyl orthoacetate (TMOA) is described. Mechanistic studies using NMR and GC-MS techniques indicate these reactions proceed via an O-methylimidate intermediate that undergoes in situ demethylation by chloride affording the corresponding acetamides. Synthetically, this reaction represents a practical, high-yielding protocol with a simple workup for the rapid conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The temperature of the solution was lowered to −20 °C, and n-butyllithium (5.5 mL of 1.6 M solution in hexane, 8.8 mmol) was injected into the flask via a syringe slowly. After the solution was stirred for 10 min at this temperature, Nmethylacetamide 37 (0.3 g, 4.2 mmol) dissolved in THF (5 mL) was added dropwise into the reaction mixture via a syringe. The reaction temperature was slowly raised to room temperature, and the mixture was allowed to stir for 30 min at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature of the solution was lowered to −20 °C, and n-butyllithium (5.5 mL of 1.6 M solution in hexane, 8.8 mmol) was injected into the flask via a syringe slowly. After the solution was stirred for 10 min at this temperature, Nmethylacetamide 37 (0.3 g, 4.2 mmol) dissolved in THF (5 mL) was added dropwise into the reaction mixture via a syringe. The reaction temperature was slowly raised to room temperature, and the mixture was allowed to stir for 30 min at ambient temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrated that MW-assisted reaction promotion with shorter reaction times (15 min) than conventional heating (1-4 h) (Scheme 15). 116 In 2010, Khan et al presented a simple methodology for the synthesis of unsymmetrical N,N 0 -disubstituted acetamidines (67). 117,118 In this paper, ethyl(1E)-N-(4-oxo-2-phenylquinazolin-3(4H)-yl)ethanimidoate (65) was rst prepared via the condensation reaction of 3-amino-2-phenyl-4(3H)-quinazolinone (64) with TEOAc (6) using acetic acid under reux conditions.…”
Section: Synthesis Of Acetamidesmentioning
confidence: 99%
“…154 In 2012, Ahmad and Silva Jr investigated the oxidation of different oxygen-containing benzo-fused cycloalkenes with various trialkyl orthoformates (4,5) in the presence of hypervalent iodine reagent [[hydroxy(tosyloxy)iodo]benzene, HTIB] under solvent-free conditions. It was found that 2H-chromenes (115) generated alkoxy-substituted 4H-chromenes (116) as the main product, along with the trans-addition product (117). On the other hand, 2H-thiochromene (118) and 4-methyl-2H-chromene (120) obtained 4H-thiochromene (119) and cis-3,4-dialkoxy-4-methyl-3,4-dihydro-2H chromenes (121), respectively (Scheme 32).…”
Section: Synthesis Of Chromanes Chromenes and Thiochromenementioning
confidence: 99%
See 1 more Smart Citation